Normy compliance w strukturze odpowiedzialności karnej za przestępstwa gospodarcze - Górski, Arkadiusz (Czasopismo Prawa Karnego i Nauk Penalnych, 2021)
The purpose of compliance norms is to ensure the lawfulness of conduct. For the theory of criminal law, they may set the standard appropriate to the rules of conduct with legal goods. The sources of compliance norms can be legally binding regulations, as well as non-binding regulations, such as codes of good practices or business habits. Therefore, the compliance norms exemplify the rules of conduct with legal good in concreto, and thus may be used to interpret criminal unlawfulness contained in the sanctioned norm in the cases of white-collar crimes, where the criminality of a given behaviour is also determined by the breach of the economic norms.